The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2486/indhealth.2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

Passive Smoking, Pulmonary Function and Bronchial Hyper-responsiveness among Indoor Sanitary Workers

Abstract: Pulmonary function parameters of 21 cleaning/sanitary women workers who have never smoked, exposed to environmental tobacco smoke (ETS) at work were compared with 34 non-exposed women workers of comparable age and other work characteristics. The studied subjects were subjected to an interview questionnaire, pulmonary function measurements, bronchial responsiveness assessment and clinical chest examination. A higher prevalence of dyspnea was found (42.9%) among exposed compared to (14.7%) among the non-exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Most the studies reported sanitation workers to be at elevated risk of respiratory infections or other adverse conditions. Fahim et al reported on BHR and found a statistically significant difference in the prevalence of dyspnea and clinical chest findings for sanitary/cleaning women workers associated with passive smoking in the workplace ( Fahim and El-Prince, 2012 ). Chandra et al examined chronic morbidity profiles for illnesses among sewage workers in India; these illnesses included pulmonary tuberculosis, COPD, bronchial asthma, hypertension, ischemic heart disease, diabetes mellitus, metabolic syndrome, and congestive heart failure ( Chandra and Arora, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most the studies reported sanitation workers to be at elevated risk of respiratory infections or other adverse conditions. Fahim et al reported on BHR and found a statistically significant difference in the prevalence of dyspnea and clinical chest findings for sanitary/cleaning women workers associated with passive smoking in the workplace ( Fahim and El-Prince, 2012 ). Chandra et al examined chronic morbidity profiles for illnesses among sewage workers in India; these illnesses included pulmonary tuberculosis, COPD, bronchial asthma, hypertension, ischemic heart disease, diabetes mellitus, metabolic syndrome, and congestive heart failure ( Chandra and Arora, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies conducted on solid waste collectors showed coughing, wheezing, phlegm, chest illness and breath problems ( 43 ), chronic bronchitis ( 44 ), and breathlessness, phlegm, coughing, and wheezing ( 45 ). From 27 studies, only one study conducted on general sanitary workers showed that they developed bronchial hyper responsiveness ( 46 ). As evidenced above, sanitary workers working as street sweepers, sewage workers, or municipal waste collectors have the possibility of developing respiratory problems if occupational safety materials aren’t well practiced.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies conducted on solid waste collectors showed coughing, wheezing, phlegm, chest illness and breath problems (43), chronic bronchitis (44), and breathlessness, phlegm, coughing, and wheezing (45). From 27 studies, only one study conducted on general sanitary workers showed that they developed bronchial hyper responsiveness (46). Categories of sanitary workers exposed to OHS problems reviewed 2000-2022.…”
Section: Discussionmentioning
confidence: 99%
“…Most the studies reported sanitation workers to be at elevated risk of respiratory infections or other adverse conditions. Fahim et al reported on BHR and found a statistically significant difference in the prevalence of dyspnea and clinical chest findings for sanitary/cleaning women workers associated with passive smoking in the workplace (Fahim and El-Prince, 2012).…”
Section: Occupational Related Respiratory Problemsmentioning
confidence: 99%